PENGARUH CERAMAH DENGAN MEDIA VIDEO ANIMASI TERHADAP PENGETAHUAN DAN SIKAP IBU DALAM PENCEGAHAN DIARE DI WILAYAH KERJA PUSKESMAS TELAGA DEWA - Meiranda, Suryani; Patroni, Rini; Darwis, Darwis (Poltekkes Kemenkes Bengkulu, 2025)
Diarrhea cases in Bengkulu Province with a percentage of 13.9%. The results of Riskesdas 2018, the prevalence of diarrhea is 8% in all age groups and 12.3% in young children, while 10.6% in infants. The study aimed to determine the effect of lectures with animated video media on mothers' knowledge and attitudes in. preventing diarrhea in the Telaga Dewa Health Center working area. Quantitative method with pre- experimental approach (one group pre test and post test). The population in the study used purposive sampling technique with a sample of 37 people. Data analysis used on knowledge and attitude is the Wilcoxon test. The results of the study the incidence of diarrhea is still high, the mother's knowledge is still lacking and the mother's attitude is still negative. The difference in knowledge and attitude before and after the intervention (p=0.000). This study shows that there is an effect of animated video media on mothers knowledge and attitudes about diarrhea prevention in the Telaga Dewa Health Center working area. Keywords: Diarrhea Prevention, Animated Video, Mother